(untitled) (Research, Society and Development, 2022)
Referred to in the past as Minotaur Syndrome, masseter hypertrophy is a relatively rare condition, with about 130 cases reported in the literature, affecting adults between twenty and thirty years, and can be diagnosed in late adolescence, without predisposition by gender. The patient may present among the clinical findings a functional disability and complaint of occlusal disharmony, although in most cases, the aesthetic complaint is the most common. It has slow, progressive, uni or bilateral growth and in the vast majority of cases presents absence of associated pain. Studies show that the intervention with Dry Needling has benefits in several cases besides myofascial pain, such as upper limb hemiparesis, trigger finger, fibromyalgia and orofacial dysfunctions. Therefore, the present study aimed to report a clinical case where the dry needling technique was used to relieve the pain of the patient diagnosed with hypertrophy of the masseter and temporal muscles, presenting satisfactory results not only in pain control but also in the patient’s aesthetics.